Kajian Organologi dan Teknik Permainan Gambus: Studi Kasus Masyarakat Desa Manyarejo Indonesia - Muhamad Rizky Nur Aliansyah; Bondan Aji Manggala (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: This study aims to describe Gambus musical instruments and Gambus playing techniques that have different tones and playing patterns. Method: this research uses descriptive qualitative research through data collection techniques received by documentation, direct observation and interviews. Results and Discussion: This research reveals that Gambus is a regional art that is played simultaneously consisting of plucked and wind instruments including a) Klung, b) Kerep, c) Thinting, d) Ajeg, and e) bass blow. The first discussion, namely organology, consists of the basic material for making Gambus musical instruments, shape and size, instrument parts, and playing techniques. Second, the playing technique consists of playing patterns, plucking patterns and wind patterns. Conclusion: The results of the study can be concluded that: (1) organology includes the basic material for making Gambus musical instruments, the shape and size of Gambus musical instruments, parts of Gambus musical instruments; (2) the technique of playing Gambus musical instruments includes the position of the left hand holding the Gambus, the right hand picking it using a pick made of bamboo. The art of Gambus music is part of the cultural tradition of the Manyarejo village community which must be developed and preserved by cultural-based education.